Cognition during active methamphetamine use versus remission. Issue 6 (3rd July 2021) - Huckans, Marilyn; Boyd, Stephen; Moncrief, Grant; Hantke, Nathan; Winters, Bethany; Shirley, Kate; Sano, Emily; McCready, Holly; Dennis, Laura; Kohno, Milky; Hoffman, William; Loftis, Jennifer M.
ABSTRACT: Objective: To evaluate whether cognitive performance in adults with active methamphetamine use (MA-ACT) differs from cognitive performance in adults in remission from MA use disorder (MA-REM) and adults without a history of substance use disorder (CTLs). Method: MA-ACT (n = 36), MA-REM (n = 48), and CTLs (n = 62) completed the Neuropsychological Assessment Battery (NAB). Results: The MA-ACT group did not perform significantly worse than CTLs on any NAB Index. The MA-REM group performed significantly (p < 0.050) worse than CTLs on the NAB Memory Index. The MA-ACT group performed significantly better than CTLs and the MA-REM group on the Executive Functions Index. Conclusions: Some cognitive deficits are apparent during remission from MA use, but not during active use; this may result in clinical challenges for adults attempting to maintain recovery and continue with treatment.